International trade and investment: still the foundation for tackling nutrition related non-communicable diseases in the era of Trump?. (4th June 2019) - Walls, Helen; Smith, Richard; Cuevas, Soledad; Hanefeld, Johanna
Abstract : Trade and investment policy strongly influence diet, nutrition, and risk of non-communicable disease—but what does this mean in the context of recent global political developments?